Gender, fraud opportunity, and rationalisation - Rashid Ameer (Journal of criminology, 2022)
Framed by opportunity and gender theories, this study examines whether men and women who occupy similar organisational positions differ in the types of fraud committed and their rationalisations. Based on 261 published legal cases of convicted fraudsters in New Zealand, our results show that fraudster's position and rationalisation are important fraud predictors. Our multinomial regression results show that there is a significant difference in the fraud committed in a similar position. There is a relationship between female gambling and embezzlement fraud. A large percentage of fraudsters of both genders offered no rationalisation; those who did, claimed they were victims of circumstances (denial of responsibility) and morally justified their offending. The morally justified rationalisation was associated with lifestyles and pleasing others. Moreover, two rationalisation categories?appeal to higher loyalties and condemning the condemners?are significant in predicting the likelihood of obtaining by deception and embezzlement fraud in the New Zealand context. We also identify two distinct patterns of fraud offending: instrumental-opportunist and pathological-opportunist.